2019
DOI: 10.1007/s40123-019-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Efficacy and Safety of 0.01% Atropine in German Schoolchildren with Progressive Myopia

Abstract: Introduction Although the interest is growing in topical low-dose atropine to control myopia in schoolchildren worldwide, its use in children of European ancestry remains controversial and solid evidence is sparse. The Oxford Centre for Evidence Based Medicine (OCEBM) classifies the evidence for this therapy as level I for East Asian populations, but only level IV in non-Asian populations. Methods Fifty-six children, aged a median of 11 years (range 6–17), were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 17 publications
2
41
0
1
Order By: Relevance
“…[55,56], but study outcomes are not conclusive and often contradictory [57,58,59]. Although several interventions, including orthokeratology [60], atropine therapy [61] and mixed defocused lenses [62] can slow down axial growth significantly, clinically effective therapies to fully normalize eye growth are not available. Understanding the etiology of myopia remains a major goal of the National Eye Institute strategic plan and Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…[55,56], but study outcomes are not conclusive and often contradictory [57,58,59]. Although several interventions, including orthokeratology [60], atropine therapy [61] and mixed defocused lenses [62] can slow down axial growth significantly, clinically effective therapies to fully normalize eye growth are not available. Understanding the etiology of myopia remains a major goal of the National Eye Institute strategic plan and Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…One small, 32-subject, case–control study in a single US pediatric ophthalmologic practice suggested that atropine 0.01% significantly reduced the rate of myopic progression over 1 year with minimal side effects [11]. Another small, uncontrolled study in Germany detected minimal pupillary dilation and an insignificant reduction in accommodation 24 h after initiating treatment [12]. The current study was designed to amplify these prior data and to assess myopia progression in a much larger, multicenter, multiethnic group of children in the USA given nightly atropine 0.01% eye drops.…”
Section: Introductionmentioning
confidence: 99%
“…They defined myopia progression of more than 0.50D or 1.0D at 1 year as rapid myopic progression. Again rates of refractive progression varied considerably between studies, risk factors for faster myopic progression in low concentration atropine studies include younger age at baseline 11,18 , higher initial myopia appropriately controlled studies to explore independent risk factors associated with rapid AL elongation in myopic children in mainland China treated with low concentration atropine.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with three other studies which explored the same relationship between baseline age and AL increase in myopic children using atropine and whose baseline profiles were similar to the current study. Joachimsen et al 11 , Wei et al 14 and Lee et al 18 found that younger children in German, mainland China and Taiwan may still progress quickly while using 0.01%, 0.01% and 0.05% atropine, respectively. It is well established that there is slowing of physiological change in AL in older children 19 We also found that the children with 0.01% atropine had a more rapid AL elongation and a worse myopic control effect than 0.02% atropine 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation